Upaya Preventif Stunting Melalui Edukasi Pada Orang Tua di Desa Serdang - Fraghini, Chitra (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2024)
Stunting is a condition in children under five which children experiences impaired growth and development due to long-term chronic malnutrition, or insufficient psychosocial stimulation. Serdang Village was recorded as a stunting village for three consecutive years with a fairly high percentage of stunting. One of the causes of the high stunting rate in Indonesia is the public's understanding of stunting. Therefore, one of the efforts to prevent and decrease stunting in Serdang village is through socialization activities. This activity is carried out through providing information and encourages families and communities to support meeting needs, raising awareness, and building commitment to behavior change. This activity was carried out in coordination with Puskesmas Rias. Providing socialization about the problem and prevention of stunting to pregnant women and mothers with children under five is an important strategy that needs to be done to increase public knowledge about the impact and dangers of stunting in children. Discuss from the results of the pre-test and posttest after the socialization was given, the participants had gained sufficient understanding regarding the definition of stunting, its causes, impacts and efforts to prevent and treat stunting in children. Providing education that is carried out regularly for Serdang Village society can be one of the right solutions to improve public health and reduce the prevelence of stunting among children in Serdang Village.